2014
DOI: 10.5455/ijmsph.2014.120920143
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypertension and its risk factors among staff of Raichur Institute of Medical Sciences, Raichur

Abstract: Background: Hypertension is a chronic condition of concern due to its role in the causation of coronary heart disease, stroke and other vascular complications. It is one of the important risk factors for cardio-vascular mortality, accounting for 20-30% of all deaths. Hypertension is an iceberg disease. To address this problem of hypertension, the theme for World Health Day, 2013 was "High Blood Pressure." Aims & Objectives: To study the prevalence of hypertension and its risk factors among staff of Raichur Ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
0
1
Order By: Relevance
“…7 A study conducted among staff of Raichur Institute of Medical Sciences found the prevalence of sedentary lifestyle to be 27%. 8 The prevalence of sedentary habits was more in our study compared to this study. The staffs in a medical college have better lifestyle practices compared to bank employees.…”
Section: Discussioncontrasting
confidence: 57%
“…7 A study conducted among staff of Raichur Institute of Medical Sciences found the prevalence of sedentary lifestyle to be 27%. 8 The prevalence of sedentary habits was more in our study compared to this study. The staffs in a medical college have better lifestyle practices compared to bank employees.…”
Section: Discussioncontrasting
confidence: 57%